Prevention of Industrial Accidents in the EU Legislation - Dariusz Materniak (Vasyl Stefanyk Precarpathian National University, 2018)
The development of civilization and technology is associated with the growing risks to the natural environment, primarily from the risks posed by industrial plants that use hazardous substances or production processes in process of production. The experience of the last few decades shows that such failures cause serious damage to the environment and material or human losses. To prevent such accidents and limit their possible consequences, legal regulations known as Seveso Directives have been developed within the European Union. They were adopted also in Poland as a EU member.